Cellular machinery for sensing mechanical force - Lim, Chul-Gyun (BMB Rep, 2018)
For mechanical force to induce changes in cellular behaviors, two main processes are inevitable; perception of the force and response to it. Perception of mechanical force by cells, or mechanosensing, requires mechanical force-induced conformational changes in mechanosensors. For this, at least one end of the mechanosensors should be anchored to relatively fixed structures, such as extracellular matrices or the cytoskeletons, while the other end should be pulled along the direction of the mechanical force. Alternatively, mechanosensors may be positioned in lipid bilayers, so that conformational changes in the embedded sensors can be induced by mechanical force-driven tension in the lipid bilayer. Responses to mechanical force by cells, or mechanotransduction, require translation of such mechanical force-induced conformational changes into biochemical signaling. For this, protein-protein interactions or enzymatic activities of mechanosensors should be modulated in response to force-induced structural changes. In the last decade, several molecules that met the required criteria of mechanosensors have been identified and proven to directly sense mechanical force. The present review introduces examples of such mechanosensors and summarizes their mechanisms of action.